Diagnosis and staging of lung cancer with the use of one single echoendoscope in both the trachea and the esophagus: a practical guide - Clementsen, Paul Frost; Bodtger, Uffe; Konge, Lars; Christiansen, Ida Skovgaard; Nessar, Rafi; Salih, Goran Nadir; Kolekar, Shailesh; Meyer, Christian Niels; Colella, Sara; Jenssen, Christian; Herth, Felix; Hocke, Michael; et al. (Endoscopic ultrasound, 2021)
Accurate staging of non-small cell lung cancer (NSCLC) is crucial for allocation to surgical, medical or multimodal treatment. EUS and endobronchial ultrasound (EBUS) have gained ground in the diagnosis and staging of lung cancer in addition to radiological imaging (e.g., computed tomography, fluoroscopy, and magnetic resonance imaging), nuclear medicine techniques (e.g. positron emission tomography, PET), combined techniques (e.g., fluorodesoxyglucosepositron emission tomography scanning), and sonographic imaging including conventional transcutaneous mediastinal and lung ultrasound. By using one single echoendoscope in both the trachea and the esophagus, surgical staging procedures (e.g. mediastinoscopy and video assisted thoracoscopy) can be avoided in a considerable proportion of patients with NSCLC.
Gesehen am 06.12.2022